FORMATION OF ENVIRONMENTAL CONSCIOUSNESS OF THE FUTURE OF TEACHERS OF BIOLOGY: GENERALIZATION RESEARCH RESULTS (Pedagogy of Higher and Secondary Education, 2008)
The results of the experimental research concerning the problem of environmental consciousness forming have been generalized in the article; the dynamics of levels in environmental consciousness forming has been canalized in the process of Biology teachers’ training.